2017
DOI: 10.1039/c7ra07120e
|View full text |Cite
|
Sign up to set email alerts
|

Assessing inter lanthanide photophysical interactions in co-doped titanium dioxide nanoparticles for multiplex assays

Abstract: This work assesses inter lanthanide photophysical interactions in titanium dioxide nanoparticles towards the development of multiplex assays.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 80 publications
(107 reference statements)
4
12
0
Order By: Relevance
“…Given the success in using semiconductor NPs to sensitize Ln 3+ * and the fact that the exciton pumping rate is not rate limiting, the possibility of incorporating more than one distinct Ln 3+ in an NP becomes a promising possibility. Indeed, experiments have demonstrated this phenomenon with the Ti­(NdSm)­O 2 NPs (average particle diameter = 2.6 ± 0.5 nm) and shown that the codoped NPs can produce nonoverlapping sharp emission bands at seven wavelengths spanning the orange-red to near-infrared spectral region, using a single excitation wavelength of 350 nm . A comparison of emission performance with their singly doped analogues indicates a decrease of Nd 3+ intensity by ∼6 times and of Sm 3+ intensity by ∼4.5 times (see Figure a).…”
Section: Resultsmentioning
confidence: 92%
See 4 more Smart Citations
“…Given the success in using semiconductor NPs to sensitize Ln 3+ * and the fact that the exciton pumping rate is not rate limiting, the possibility of incorporating more than one distinct Ln 3+ in an NP becomes a promising possibility. Indeed, experiments have demonstrated this phenomenon with the Ti­(NdSm)­O 2 NPs (average particle diameter = 2.6 ± 0.5 nm) and shown that the codoped NPs can produce nonoverlapping sharp emission bands at seven wavelengths spanning the orange-red to near-infrared spectral region, using a single excitation wavelength of 350 nm . A comparison of emission performance with their singly doped analogues indicates a decrease of Nd 3+ intensity by ∼6 times and of Sm 3+ intensity by ∼4.5 times (see Figure a).…”
Section: Resultsmentioning
confidence: 92%
“…This hypothesis was validated by performing control experiments with the Ti­(NdEr)­O 2 . In this system, the Nd 3+ near-infrared and Er 3+ visible emission decreases with respect to that in the corresponding singly doped NPs, however the Er 3+ near-infrared emission increases by ∼3 times in the codoped NPs (see Figure b, d) . Thus, “cross-talk” among Ln dopants will become an important new design constraint.…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations